2019
DOI: 10.2147/dhps.s187829
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pattern of medication use in geriatric patients at primary healthcare facilities in Karawang, Indonesia</p>

Abstract: BackgroundRational drug use is a critical component in patient care, particularly among the elderly who often have multiple medical problems. The aim of this study was to assess the pattern of medication use among the elderly visiting primary health care facilities.MethodsA retrospective cross-sectional study was conducted at 25 primary health care facilities in Karawang District, Indonesia, and patients aged ≥60 years visiting the facilities from January to December 2014 were included. A systematic random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
1
7
3
3
Order By: Relevance
“…Our result was supported by the studies conducted in Ethiopia (96.6%), 4 Egypt (95.4%), 15 Lao People's Republic (86.2%) 26 and Indonesia (83.07%). 11 However, lower value as compared to this study was also reported in Serbia (70%) 27 and India (66%). 25 WHO issued EML to ensure rational prescribing, like using an optimal drug?…”
Section: Prescribing Indicatorscontrasting
confidence: 65%
See 4 more Smart Citations
“…Our result was supported by the studies conducted in Ethiopia (96.6%), 4 Egypt (95.4%), 15 Lao People's Republic (86.2%) 26 and Indonesia (83.07%). 11 However, lower value as compared to this study was also reported in Serbia (70%) 27 and India (66%). 25 WHO issued EML to ensure rational prescribing, like using an optimal drug?…”
Section: Prescribing Indicatorscontrasting
confidence: 65%
“…4,15 The generic prescribing was at a level of 30% with the lowest value was recorded in MOD (23.7%). Similarly, the recent finding was lower than the studies carried out in Ethiopia (98.7%), 4 Indonesia (98.09%), 11 Timor-Leste (92%) 23 and Nigeria (49.3%). 21 Furthermore, our finding was higher than the studies carried out in Andorra (6%) 24 and Ludhiana India (25%).…”
Section: Prescribing Indicatorscontrasting
confidence: 55%
See 3 more Smart Citations